Corruption in Customs - Chalendard, Cyril; Fernandes, Ana M.; Raballand, Gael; Rijkers, Bob (World Bank, Washington, DC, 2021)
This paper presents a new methodology to detect corruption in customs and applies it to Madagascar’s main port. Manipulation of assignment of import declarations to inspectors is identified by measuring deviations from random assignment prescribed by official rules. Deviant declarations are more at risk of tax evasion, yet less likely to be deemed fraudulent by inspectors, who also clear them faster. An intervention in which inspector assignment was delegated to a third party validates the approach, but also triggered a novel manifestation of manipulation that rejuvenated systemic corruption. Tax revenue losses associated with the corruption scheme are approximately 3 percent of total taxes collected and highly concentrated among a select few inspectors and brokers.